Effect of frictional frequency on the subsurface evolution of 316L stainless steel in tribocorrosion and its influence on the synergistic effect between corrosion and wear. (February 2023) - Wu, Yinchao; Wang, Zhongwei; Chen, Jiaolong; Ma, Yanlong; Yan, Yu; Qiao, Lijie
Abstract: This study investigated the effect of frictional frequency on the subsurface evolution of 316L stainless steel in tribocorrosion and its influence on the synergistic effect between corrosion and wear. The stainless steel was worn in sulfuric acid solution at different frictional frequencies with sliding distance of 28.8 m at passive/cathodic potentials of ± 0.4 V vs . Ag/AgCl, and then the worn surface and subsurface were characterized. The results indicated that the frictional frequency showed a non-monotonic influence on the tribocorrosion behavior of the stainless steel: the material loss volume first decreased and then increased with the increasing frequency from 0.5 to 3 Hz. It was found that the non-monotonic influence was caused by the influence of frictional frequency on the subsurface microstructure.